Towards a Theory of Self-Segregation as a Response to Relative Deprivation: Steady-State Outcomes and Social Welfare - Oded Stark; You Qiang Wang (Economics and Happiness: Framing the Analysis, 2005)
We model group formation as a response to relative deprivation. We employ two measures of relative deprivation. We show that in the case of each of these measures the process of deprivation-induced self-selection into groups reaches a steady state, and that the steady-state distribution differs from the distribution that would have obtained had group affiliation been chosen so as to maximize rank. We study the social welfare implications of the deprivation-induced process of group formation and show that when individuals are left to pursue their betterment, the resulting state tends to fall short of the best social outcome. We present several implications of the model including federalism and the demand for secession.
Keywords: 330